IDENTIFIKASI POTENSI DAMPAK LINGKUNGAN POTENSIAL PADA INDUSTRI FURNITURE - Afifah, Silvy Nur; Yuliawati, Evi (Jurnal Ilmiah Teknik Industri, 2024)
The company's production process produces several wastes and emissions. One aspect is due to the use of energy and materials, which causes environmental problems and decreases the availability of resources. This research will investigate the influence of environmental impacts on production sustainability in furniture companies. The impact assessment produced by OpenLCA software can provide information for companies to make improvements in the production process. The potential environmental impact on furniture companies is obtained based on the impact value produced in the production of Vasari mirrors. The results from the OpenLCA software obtained an Aquatic eutrophication EP(P) impact value of 24,747 Pt, a Human toxicity water impact value of 13,536 Pt and a Radioactive waste impact value of 9,201 Pt. Next, the influence of the three highest potential environmental impacts was analyzed using multiple linear regression. Of several alternative repair efforts, replacing the alkyl paint material with polyester resin, and the cerium oxide material with a wool polishing wheel (organic sheep farm) produces the smallest impact value. The potential environmental impact value after repairs is the Aquatic eutrophication EP(P) value of 24,746 Pt, the Human toxicity water value of 13,534 Pt, and the Radioactive waste value of 9.2 Pt.